Towards consensus measurement standards for patient-centered outcomes. (July 2019) - Cano, S.J.; Pendrill, L.R.; Melin, J.; Fisher, W.P.
Highlights: PCO measures offer the opportunity for more meaningful measurement of health outcomes. PCO measures are currently not capable of delivering quality assured measurement. Solution 1: use mathematical models to define additive units of measurement. Solution 2: establish coordinated international networks of key stakeholders. Solution 3: better use of technology to leverage measurement through item banks. Abstract: Patient centered outcomes pertain to a patient's beliefs, opinions and needs in conjunction with a clinician's medical expertise and assessment. The rise of patient-centered outcome (PCO) measurement parallels increased interest in patient-centered care. PCO measures offer the opportunity for more meaningful measurement of health outcomes informative enough to guide treatment decisions. However, it has been suggested that, for practical and scientific reasons, existing PCO measures are currently not capable of delivering the kind of quality assured measurement required for high-stakes decision making. Potential solutions include: addressing the lack of units in PCO measurement through recourse to mathematical models devised to define meaningful, invariant, and additive units of measurement with known uncertainties; establishing coordinated international networks of key stakeholders guided by five principles (i.e., collaboration, alignment, integration, innovation and communication); better use of technology leveraging measurement through item banks linking PCO reports via common items, common patients, or specification equations based in strong explanatory theory. And finally ensuring PCO measurement always is associated with: (1) a clear definition of the measurand in regards to the intended clinical use; (2) a clear definition of the clinically allowable error of measurement; (3) international cooperation and consensus to navigate the complexities of the development of metrologically sound reference measurement systems; and (4) continued clinical validation of newly calibrated measures. In this article, we illustrate the principles to improve PCO measures with examples from breast cancer, vision-related patient-reported outcome measures, and dementia clinician-reported and performance outcome measures.